Sensibiliser à la diversité : la formation aux enjeux interculturels dans les programmes universitaires en relation d’aide au Québec - Beaudoin-Julien, Andrée-Anne; Demers, Valérie; Leanza, Yvan (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
This study describes and compares the availability of courses exploring intercultural issues in Quebec university programs for four disciplines of the caring professions (occupational therapy, social work, psychology and midwifery). The study identifies the presence of such courses in each discipline, their mandatory or optional nature, their pedagogical characteristics and their content. The themes describing this content, identified through inductive content analysis, were grouped together according to the components of cultural competence: cultural self-awareness, cultural knowledge and skills (Sue et al., 1992). Cultural knowledge is most often addressed, except in midwifery, where it is cultural skills. Almost a quarter of programs do not offer any intercultural courses. The courses offered are mostly lectures, although an experiential format (e.g., internship or practicum) would rather help to develop cultural competence. The discussion highlights the advantages and disadvantages of making these intercultural courses mandatory, notably regarding students’ motivation, and suggests concrete actions facilitating the necessary institutional changes.